2006
DOI: 10.1016/j.ydbio.2006.08.052
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of cytoskeletal and motility proteins in the sea urchin genome assembly

Abstract: The sea urchin embryo is a classical model system for studying the role of the cytoskeleton in such events as fertilization, mitosis, cleavage, cell migration and gastrulation. We have conducted an analysis of gene models derived from the Strongylocentrotus purpuratus genome assembly and have gathered strong evidence for the existence of multiple gene families encoding cytoskeletal proteins and their regulators in sea urchin. While many cytoskeletal genes have been cloned from sea urchin with sequences already… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0
2

Year Published

2008
2008
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 114 publications
2
41
0
2
Order By: Relevance
“…sequences not yet determined, the predicted sequences from the Chlamydomonas genome database were used (see Materials and Methods). The single-headed DHC type can be classified into three subgroups, IAD3, IAD4, and IAD5 types, as reported previously (Morris et al, 2006;Wickstead and Gull, 2007). Minor DHCs identified in this study are indicated by arrowheads.…”
Section: Function Of Minor Dhcs and Mechanism Of Their Localizationsupporting
confidence: 71%
See 2 more Smart Citations
“…sequences not yet determined, the predicted sequences from the Chlamydomonas genome database were used (see Materials and Methods). The single-headed DHC type can be classified into three subgroups, IAD3, IAD4, and IAD5 types, as reported previously (Morris et al, 2006;Wickstead and Gull, 2007). Minor DHCs identified in this study are indicated by arrowheads.…”
Section: Function Of Minor Dhcs and Mechanism Of Their Localizationsupporting
confidence: 71%
“…7, Table 1). As shown in recent studies (Morris et al, 2006;Wickstead and Gull, 2007;Wilkes et al, 2008), single-headed DHCs as a whole makes up a single large family which can be further classified into three groups: group IAD3 comprising DHC4, DHC5 (the DHC of dynein b), DHC6 (dynein a), DHC8 (dynein e), DHC9 (dynein c) and DHC11; group IAD4 comprising DHC2 (dynein d); and group IAD5 comprising DHC3 and DHC7 (dynein g; Fig. 7).…”
Section: Journal Of Cell Science 122 (9)mentioning
confidence: 96%
See 1 more Smart Citation
“…In urchin larvae, the cytoskeleton regulates basic aspects of development, such as cell migration, mitosis and cytokinesis, organelle movements, ciliary and flagellar movements and cell shape changes [70], and the protection of cytoskeletal function is likely to be important for the completion of development. Transcriptomic and proteomic analysis of mussels (Mytilus spp.)…”
Section: Discussionmentioning
confidence: 99%
“…They produce a large number of synchronously developing transparent embryos that can be easily manipulated. Using sea urchin as a model organism, the sea urchin community has contributed to our understanding of the fertilization process [18][19][20][21] , cell biological processes [22][23][24] , and the gene regulatory networks (GRNs) [25][26][27][28] .…”
Section: Introductionmentioning
confidence: 99%